2009
DOI: 10.1097/qad.0b013e32831c54e5
|View full text |Cite
|
Sign up to set email alerts
|

HIV monotherapy with ritonavir-boosted protease inhibitors: a systematic review

Abstract: The overall efficacy of ritonavir-boosted protease inhibitor monotherapy is inferior to HAART. The efficacy improves in patients started on monotherapy after suppressed HIV-RNA for at least 6 months. Ten percent of patients have viral rebound with HIV-RNA levels between 50 and 500 copies/ml. Possible explanations are lack of HIV suppression in particular cells or compartments, alternative resistance mechanisms, and nonadherence. Once proven that reintroduction of NRTIs, in patients with loss of viral suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 32 publications
6
105
0
1
Order By: Relevance
“…Rates of resistance mutations were similar between arms, as was overall neurocognitive function. Even with the inclusion of the results from new studies, the findings of the present study are similar to those of two previous meta-analyses [20,21].…”
Section: Discussionsupporting
confidence: 89%
“…Rates of resistance mutations were similar between arms, as was overall neurocognitive function. Even with the inclusion of the results from new studies, the findings of the present study are similar to those of two previous meta-analyses [20,21].…”
Section: Discussionsupporting
confidence: 89%
“…10,11,[13][14][15] The barrier to resistance of bPIs is also high compared with nucleoside and non-nucleoside analogues. Additionally, the non-overlapping resistance profile with other available ARV drug classes would mean that existing standard triple-drug regimens for symptomatic patients would be unaffected as both nucleoside reverse transcriptase inhibitors (NRTI) and non-nucleoside reverse transcriptase inhibitors (NNRTI) would be preserved.…”
Section: Ways Forwardmentioning
confidence: 99%
“…1 However, two systematic reviews have shown a higher rate of virological failure in patients who switched to PI monotherapy compared to those who received standard triple combination therapy. 2,3 In previous studies of PI monotherapy as a switch option, patients with higher nadir CD4 counts, baseline HIV RNA < 1 copy/mL, and high adherence to treatment have been most likely to achieve sustained HIV RNA suppression of <50 copies/mL. [4][5][6] A meta-analysis of 10 clinical trials has shown a significantly higher risk of antiretroviral treatment failure in patients co-infected with hepatitis C virus (HCV).…”
mentioning
confidence: 99%